1998
DOI: 10.1139/f97-224
|View full text |Cite
|
Sign up to set email alerts
|

Responsiveness of the interrenal tissue of yellow perch (Perca flavescens) from contaminated sites to an ACTH challenge test in vivo

Abstract: The effects of chronic toxic stress on the hypothalamo-pituitary-interrenal (HPI) axis were investigated in yellow perch (Perca flavescens) captured at a reference site (Lake Memphremagog) and two sites contaminated with heavy metals and organic contaminants (Ile Perrot and Iles de la Paix, Lake St. Louis) in spring, summer, and fall. Cortisol secretion of the fish was stimulated in situ by an acute capture stress or by an i.p. injection of 4 IU/100 g body mass of porcine corticotropin (ACTH1-39). The response… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
30
1

Year Published

1998
1998
2021
2021

Publication Types

Select...
10

Relationship

4
6

Authors

Journals

citations
Cited by 61 publications
(33 citation statements)
references
References 44 publications
2
30
1
Order By: Relevance
“…ACTH stimulated the StAR gene expression in the seabream head kidney preparations by binding to its specific membrane receptors, as demonstrated when 1 mM CIP, an antagonist of the ACTH receptor (Li et al 1978), effectively blocked the ACTHstimulated StAR expression in our in vitro model, without affecting the basal levels of StAR expression. The rapid increase in cortisol levels, which we observed after ACTH treatment, is in agreement with several previous studies conducted under various experimental conditions (Donaldson 1981, Nichols & Weisbart 1984, Girard et al 1998, Pottinger & Carrick 2001, Hagen et al 2006. It also agrees with the previous data found in the same species, S. aurata, in our laboratory (Rotllant et al 2001, Ganga et al 2006 showing that ACTH caused a rapid increase in cortisol levels in superfused head kidney tissue.…”
Section: Discussionsupporting
confidence: 93%
“…ACTH stimulated the StAR gene expression in the seabream head kidney preparations by binding to its specific membrane receptors, as demonstrated when 1 mM CIP, an antagonist of the ACTH receptor (Li et al 1978), effectively blocked the ACTHstimulated StAR expression in our in vitro model, without affecting the basal levels of StAR expression. The rapid increase in cortisol levels, which we observed after ACTH treatment, is in agreement with several previous studies conducted under various experimental conditions (Donaldson 1981, Nichols & Weisbart 1984, Girard et al 1998, Pottinger & Carrick 2001, Hagen et al 2006. It also agrees with the previous data found in the same species, S. aurata, in our laboratory (Rotllant et al 2001, Ganga et al 2006 showing that ACTH caused a rapid increase in cortisol levels in superfused head kidney tissue.…”
Section: Discussionsupporting
confidence: 93%
“…Lifelong exposure of brown trout (Salmo trutta) to waterborne Cd and Zn (Norris et al, 1999) and 5-day dietary exposure of tilapia (Oreochromis mossambicus) to PCB (Quabius et al, 1997) have been found to result in a delayed cortisol response to acute disturbance by con"nement. In the present study, however, the level of plasma cortisol reached was not observed to be decreased (Quabius et al, 1997;Girard et al, 1998;Norris et al, 1999;Lappivaara, 2000) by the prevailing exposure to BKMEs. This contrasts with some other "eld studies (Hontela et al, 1992(Hontela et al, , 1995(Hontela et al, , 1997, in which the time-dependent progression of cortisol response has not, however, been elucidated by a serial data grouping.…”
Section: Discussioncontrasting
confidence: 85%
“…Lake Memphremagog, located in the Eastern Townships (approximately 125 km east of Montreal) and remote from any industrial activity (Girard et al 1998), was sampled and included in the set of reference lakes. Lake St. Louis, a fluvial lake in the St. Lawrence River immediately west of the island of Montreal, receives pollutant loading from multiple sources (Hontela et al 1992).…”
Section: Study Sitesmentioning
confidence: 99%